Sámi Shamanism Past and Present and the Desecration of the Sacred in Finland - Joy, Francis (Lapin yliopisto, Arktinen keskus, 2016)
The aim of the paper is to outline a number of prospective legal issues in relation to Sámi shamanism and culture within a discussion about Sámi cultural heritage